As interest rates surge: Flighty deposits and lending - Giuseppe Cappelletti; David Marqués Ibá\~nez; Alessio Reghezza; Carmelo Salleo (European Central Bank (ECB), 2024)
How a historic drop in bank deposits shapes banks' loan supply? We exploit the effects of a large, and unexpected, increase in monetary policy rates to estimate the deposit channel of monetary policy using an extensive credit register that includes all bank-firm lending relationships in all euro area countries. We find that banks experiencing large deposit outflows reduce credit, but not the interest rate they charge, to the same borrower relative to other lenders. This credit restriction is stronger for fixed rate and longer maturity loans, but not for riskier borrowers. The effect is mostly driven by banks coming into the hiking period with a larger unhedged duration gap that renders borrowers of those banks more vulnerable to credit restrictions due to the deposit outflows as interest rates surge. We resort to the deposit beta as an instrument variable and a matched estimator that bear out the thrust of our results.
Keywords: E51; E58; G21; 330; Monetary policy; Banks; Bank deposits